Prove by induction: \sum_{k=1}^{n} \binom n k = 2^n -1 for all n\in \mathbb{N}.
Today I wrote calculus exam, I had this problem given.
I have the feeling that I will get 0 points for my solution, because I did this:
Base Case: n=1
\sum_{k=1}^{1} \binom 1 1 = 1 = 2^1 -1 .
Induction Hypothesis: for all n \in \mathbb{N}:
\sum_{k=1}^{n} \binom n k = 2^n -1
Induction Step: n \rightarrow n+1
\sum_{k=1}^{n+1} \binom {n+1} {k} = \sum_{k=1}^{n} \binom {n+1} {k} + \binom{n+1}{n+1} = 2^{n+1} -1
Please show me my mistake because next time is my last chance in this class.
Answer
Your first mistake is that you stated the induction hypothesis incorrectly: it should be simply that
\sum_{k=1}^n\binom{n}k=2^n-1\;.\tag{1}
What you gave as induction hypothesis is actually the theorem that you’re trying to prove!
Now, assuming (1) you want to prove that \sum_{k=1}^{n+1}\binom{n+1}k=2^{n+1}-1\;.
This is an occasion when it’s not a good idea to split off the last term. Instead, use the Pascal’s triangle identity for binomial coefficients:
\begin{align*} \sum_{k=1}^{n+1}\binom{n+1}k&=\sum_{k=1}^{n+1}\left(\binom{n}k+\binom{n}{k-1}\right)\\\\ &=\sum_{k=1}^{n+1}\binom{n}k+\sum_{k=1}^{n+1}\binom{n}{k-1}\\\\ &\overset{*}=\sum_{k=1}^n\binom{n}k+\sum_{k=0}^n\binom{n}k\\\\ &=\left(2^n-1\right)+\binom{n}0+\sum_{k=1}^n\binom{n}k\\\\ &=2^n-1+1+2^n-1\\\\ &=2\cdot2^n-1\\\\ &=2^{n+1}-1\;. \end{align*}
At the starred step I used the fact that \binom{n}{n+1}=0 to drop the last term of the first summation, and I did an index shift, replacing k-1 by k, in the second summation.
No comments:
Post a Comment